2001
DOI: 10.1046/j.1445-2197.2001.02220.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of amylase and lipase in the diagnosis of acute pancreatitis

Abstract: Serum lipase is recommended for diagnosis of AP, both early and late in the disease. Although highly specific when elevated, all pancreatic enzymes have low sensitivity for diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 21 publications
5
65
2
2
Order By: Relevance
“…There is still a controversy over the diagnostic value of serum lipase activity in feline AP (4, 7), which may be of some help in the diagnosis of human and canine disease (20)(21). In this study, we noticed an increase of serum lipase activity 8 hours after induction of pancreatitis that remained high until the 8 th and then until the 16 th day postoleic acid infusion.…”
Section: Discussionsupporting
confidence: 49%
“…There is still a controversy over the diagnostic value of serum lipase activity in feline AP (4, 7), which may be of some help in the diagnosis of human and canine disease (20)(21). In this study, we noticed an increase of serum lipase activity 8 hours after induction of pancreatitis that remained high until the 8 th and then until the 16 th day postoleic acid infusion.…”
Section: Discussionsupporting
confidence: 49%
“…Treacy et al had found a sensitivity of 45% for serum amylase using three times the upper limit of normal values for serum amylase as the cut off for diagnosis. 10 The findings of sensitivity in our study correlates closely to that by Treacy et al However, Kempainnem 11 et al and Ventrucci 12 et al found a higher sensitivity of about 83% and 88% respectively. This might be because both the study used serum amylase for the diagnosis of acute pancreatitis, while Treacy et al like us used USG for the diagnosis of acute pancreatitis.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is consistent with the findings proposed in the study of Owen J. O'Connor, Sebastian McWilliams et al 10 In the present study, the elevated serum lipase was found to have higher sensitivity (89.09%) in detecting the acute pancreatitis than the serum amylase (65.4%). This finding is similar to that of the study done by Treacy J et al 11 The higher sensitivity of both in the present study may be due to the fact that most of the cases were of severe pancreatitis and the small study group. In the present study, there were five cases (19.04%) which had vascular complications.…”
Section: Prognostic Criteria Used For Evaluation Modified Ct Severitysupporting
confidence: 81%